College Electrical Equipment Registration Management System (CEERMS) / Nurul Nadiah Mohd Sohaini - Mohd Sohaini, Nurul Nadiah (2017)
Managing student registration for electrical equipment is one of the important part for college in the university. Unit Pengurusan Kolej Kerawang (UPKK) is managing the process manually which requires students to fill in their information and its compiled using Microsoft Excel. The process is time consuming, require a lot of paper usage and need to spend budget on the stickers. College Electrical Equipment Registration Management System (CEERMS) was developed to assist UPKK to handle the registration record in a systematic way. The user of this system can be divided into three which are administrator, student and staff. The methodology used to develop CEERMS is a Rapid Application Development (RAD). CEERMS was evaluated by the experts and users. The questionnaire is distributed to the 30 respondents and evaluated based on six constructs which are ease of use, interface, web-based application, user experience, usability and satisfaction. Result shows that respondents agreed on satisfaction construct with the highest mean which is 4.83 (SD=0.379). As for future enhancement, one possible module that can be added in CEERMS is the system may able to record the newly registered item and gives advantage to the users.